Volumetric alterations in the heteromodal association cortex in children with autism spectrum disorder - Kalmar, Julia; Poustka, Luise; Haffner, Johann; Parzer, Peter; Henze, Romy (European psychiatry, 2015)
We investigated if alterations in higher-order association areas related to schizophrenia, namely the heteromodal association cortex (HASC), are also observable in subjects with autism spectrum disorder (ASD). A group of 18 children with ASD and 18 healthy controls (HC) underwent magnetic resonance imaging (MRI). The examination comprised an analysis of group differences in gray matter (GM) volume, surface area (SA) and hemispheric lateralization. Differences in GM volumes in children with ASD and HC were detected in frontal and parietal areas related to the HASC. No HASC structure that showed changes in GM volume exhibited differences in SA. Alterations in hemispheric lateralization between ASD and HC are seen in a frontal area of the HASC. Our results indicate that changes in HASC areas are not restricted to schizophrenia, but extend to other psychiatric disorders, namely ASD. The lacking group differences in SA indicate that changes in GM volume are possibly evoked by other variables than SA in children with ASD.